2021
DOI: 10.1021/acsaem.0c02771
|View full text |Cite
|
Sign up to set email alerts
|

High Ionic Conductivity of Liquid-Phase-Synthesized Li3PS4 Solid Electrolyte, Comparable to That Obtained via Ball Milling

Abstract: Recently, several sulfide solid electrolytes have been synthesized by liquid-phase synthesis for the commercialization of all-solid-state batteries. Unfortunately, the ionic conductivity for most of these electrolytes is unsatisfactory compared to that of solid electrolytes synthesized by conventional ball milling. This problem is attributed to different mechanisms between the liquid phase and the solid phase in reaction and formation. However, to the best of our knowledge, the effect of the solvent on the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…The precursor powders in ACN and THP both exhibited three steps of weight loss. Several studies have demonstrated that forward DTA scans of Li 3 PS 4 complexes containing organic solvent exhibit large endothermic peaks 13 , 14 . Further, the decomposition reaction of Li 7 P 3 S 11 to Li 4 P 2 S 6 , Li 3 PS 4 , and sulfur occurs at a temperature higher than 280°C 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The precursor powders in ACN and THP both exhibited three steps of weight loss. Several studies have demonstrated that forward DTA scans of Li 3 PS 4 complexes containing organic solvent exhibit large endothermic peaks 13 , 14 . Further, the decomposition reaction of Li 7 P 3 S 11 to Li 4 P 2 S 6 , Li 3 PS 4 , and sulfur occurs at a temperature higher than 280°C 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the dielectric constant, the donor number may also play a role in reactivity.
Figure 5 ( a ) Nyquist plot and ( b ) ionic conductivity at room temperature for 70Li 2 S–30P 2 S 5 system formed via Dox, THP, and ACN solvents as a function of dielectric constant together with those of 70Li 2 S–30P 2 S 5 system formed via other solvents 12 14 . The white circles indicate reference values.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations